2022-RA-679-ESGO Prevalence of HPV infection among young women in Almaty, Kazakhstan. (20th October 2022) - Satanova, Alima; Kaydarova, Dilyara; Kukubassov, Yerlan; Bolatbekova, Raikhan; Aliyeva, Saadat; Bertleuov, Orynbassar; Kaldybekov, Dauren; Pak, Roza
Abstract : Introduction/Background: According to Globocan, in 2020, 353, 497 cases of morbidity and 200, 736 deaths from cervical cancer were registered in the Republic of Kazakhstan. Despite the introduction since 2008 of the National CC Screening Program, morbidity and mortality rates from this disease remain high. Methodology: In this cross-sectional study, we assessed the prevalence of HPV types among young women aged 18 to 30 in Almaty, Kazakhstan, starting in September. 2021 to April 2022. The study was conducted at the Kazakh Research Institute of Oncology and Radiology. Results: Of the 235 samples examined, 42 were positive for any type of HPV. The overall incidence was 17.8%. When stratified by age groups (18–25 years and 25–30 years), there was an exceptional prevalence of HPV among age groups, with a higher prevalence of HPV infection in the 18–25 year group than in the 25–30 year group. HPV prevalence, and HPV high risk of increase depending on age, the highest among 18–25 years of age and increase in frequency at older ages. The prevalence of typical HPV HR is 9.7%. All respondents had several types of HPV. The most common HPV types were HPV 16, 18, 31 types in 23 (9.7%). HPV 33, 35, 56 types in 10 (4.2%) cases. HPV 39, 45, 59 types in 6 (2.5%) cases, HPV 51, 52, 58 in 3 (1.2%) cases. Conclusion: Thus, we report a high prevalence of any type of HPV and HR-HPV types in sexually active young women aged 18–25 years, with a higher prevalence of high-risk HPV types also observed in women in this age group. These data provide information that can be used in HPV prevention policy as a comparison after the implementation of the HPV vaccination program in subsequent years.